The Commercial Lease: Property or Contract - Brock, Jason; Phillips, Jim (Alberta Law Review, 2001)
The commercial lease has historically been treated as a conveyance of an interest in land which creates a property-based relationship between the lessor and lessee, despite the fact that the relationship is created by contract and could be seen as a contract for the ongoing use of the land. Some Canadian cases, however, have applied "partial contractualization " — using both property and contract rules and concepts to interpret leases. The article examines the historical development of the lease and its treatment in Canadian courts, as well as in other common law courts. The authors argue that the property/contract hybrid should be eliminated in favour of "complete contractualization " — using pure contract principles to interpret the commercial lease. The article points out how contract principles would serve the parties to the lease just as well, or better, than property principles and offers solutions for the anticipated problem area of security of tenure for the tenant.

African Legal Developments in the United States and Sub-Saharan Africa - Eisenfeld, Jamie; Serres, Francois (The International Lawyer, 2001)

Les formes actuelles de négoce en Afrique (Nigeria, Côte-d'Ivoire, Bénin). - Dovonou, Florent (Publications de la Société française d'histoire des outre-mers, 2001)

L'évolution du rôle des juges dans le développement des systèmes juridiques africains - N’Diaye, Cheikh (Les Cahiers de droit, 2001)
Un article de la revue Les Cahiers de droit, diffusée par la plateforme Érudit.

La mondialisation, le droit et la justice - Nicora, Pierre (Les Cahiers de droit, 2001)
Un article de la revue Les Cahiers de droit, diffusée par la plateforme Érudit.

Das einheitliche Kaufrecht der afrikanischen OHADA-Staaten im Vergleich zum UN-Kaufrecht - Schroeter, Ulrich G. (Recht in Afrika, 2001)
Keywords: International sale of goods; UN Convention on Contracts for the International Sale of Goods (1980); Uniform law

L'achat par la société de ses propres actions : esquisse d'une étude comparative entre le droit français et le droit uniforme OHADA - Shamsidine, Adjita Akrawati (Revue internationale de droit économique, 2001)